An experimental study on optimizing parameters for sand consolidation with organic-inorganic silicate solutions - Saurabh Mishra; Geetanjali Chauhan; Keka Ojha (Petroleum, 2024)
Sand production along with the oil/gas detrimentally affects the oil production rate, downhole & subsurface facilities. Mechanical equipment and various chemicals like epoxy resin, furan resin, phenolic resin, etc. are used in the industry to reduce or eliminate this problem. In the present study, a blend of organic and inorganic silicates are used to consolidate loose sand in the presence and absence of crude oil using a core flooding apparatus. The effects of chemical concentration, pH, curing temperature and time, and the presence of residual oil on the consolidation treatment results such as compressive strength and permeability retention, were investigated and optimized. FT-IR and FE-SEM characterization techniques were employed to investigate the interaction between the chemical molecules and the sand grains. The current binding agent exhibited a viscosity of less than 6 cP at room temperature, which facilitates efficient pumping of binding agent into the desired formation through the well bore. The developed mixture demonstrated consolidation properties across all pH conditions. Furthermore, during the experimental investigation, the curing time and temperature was carefully optimized at 12 h and 423.15K, respectively to achieve the highest compressive strength of 2021 psi while achieving the permeability retention of 64%. The current chemical system exhibited improved consolidation capacity and can be effectively utilized for sand consolidation treatment in high-temperature formations.